The European Union and the United States : competition, convergence and crisis in the global arena - Smith, Michael, 1947-; Guay, Terrence R.; Morgenstern-Pomorski, Jost-Henrik (London ; New York ; Oxford ; New Delhi ; Sydney : Bloomsbury Academic, 2025)
This revised edition offers a comprehensive analysis of the evolving relationship between the European Union and the United States. Framed around themes of competition, convergence, and crisis, the book explores transatlantic dynamics in trade, political economy, foreign policy, and global governance. It incorporates contemporary issues such as cybersecurity, climate change, populism, and the rise of emerging powers, providing a holistic and interdisciplinary perspective on EU–US relations. Designed for advanced undergraduate and postgraduate students, it includes case studies, summary tables, and speech extracts to support deeper understanding.
Kniha analyzuje vztahy mezi Evropskou unií a Spojenými státy v kontextu globální politiky, se zaměřením na konkurenci, konvergenci a krize. Autoři zkoumají vývoj transatlantických vztahů, politické a ekonomické interakce a dopady současných globálních výzev na strategické partnerství mezi EU a USA.
Obsahuje bibliografické odkazy a rejstřík
Keywords: Evropská unie; mezinárodní vztahy; zahraniční vztahy; zahraniční politika; politiky Evropské unie; konvergence (ekonomie); konkurenceschopnost; země Evropské unie; Spojené státy americké; kolektivní monografie; international relations; foreign relations; foreign policy; European policies; convergence (economics); competitiveness; European Union countries; United States; collective monographs